Catalytic Difunctionalization of Unactivated Alkenes with Unreactive Hexamethyldisilane through Regeneration of Silylium Ions. Issue 48 (23rd October 2019) - Wu, Qian; Roy, Avijit; Irran, Elisabeth; Qu, Zheng‐Wang; Grimme, Stefan; Klare, Hendrik F. T.; Oestreich, Martin
Abstract: A metal‐free, intermolecular syn ‐addition of hexamethyldisilane across simple alkenes is reported. The catalytic cycle is initiated and propagated by the transfer of a methyl group from the disilane to a silylium‐ion‐like intermediate, corresponding to the (re)generation of the silylium‐ion catalyst. The key feature of the reaction sequence is the cleavage of the Si−Si bond in a 1, 3‐silyl shift from silicon to carbon. A central intermediate of the catalysis was structurally characterized by X‐ray diffraction, and the computed reaction mechanism is fully consistent with the experimental findings. Abstract : Come together : A highly reactive silylium ion brings together two unreactive reactants while being consumed and regenerated during the catalytic cycle. Unactivated alkenes are thus converted into 1, 2‐bissilylated alkanes using simple hexamethyldisilane. The Si−Si bond is cleaved during this process in a kinetically and thermodynamically favored 1, 3‐silyl shift from silicon to carbon, as supported by quantum‐chemical calculations.